2020
DOI: 10.3390/v12121348
|View full text |Cite
|
Sign up to set email alerts
|

The DDX23 Negatively Regulates Translation and Replication of Foot-and-Mouth Disease Virus and Is Degraded by 3C Proteinase

Abstract: DEAD-box helicase 23 (DDX23) is a host nuclear helicase, which is a part of the spliceosomal complex and involved in pre-mRNA splicing. To investigate whether DDX23, an internal ribosomal entry sites transacting factor (ITAF) affects foot-and-mouth disease virus (FMDV) replication and translation through internal ribosome entry site (IRES)-dependent manner. For this, we utilized a pull-down assay, Western blotting, quantitative real-time PCR, confocal microscopy, overexpression and small interfering RNA knockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
3
10
0
Order By: Relevance
“…Similarly, the crucial FMDV protease 3C pro participates in the frontline defense of the virus to maintain viral integrity by inhibiting the host IFN response [ 58 ]. Our previous study confirmed that FMDV 3C pro degrades DDX23 to antagonize its antiviral activity [ 35 ].…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…Similarly, the crucial FMDV protease 3C pro participates in the frontline defense of the virus to maintain viral integrity by inhibiting the host IFN response [ 58 ]. Our previous study confirmed that FMDV 3C pro degrades DDX23 to antagonize its antiviral activity [ 35 ].…”
Section: Introductionsupporting
confidence: 73%
“…Target proteins were pulled down using the Pierce Magnetic RNA-Protein Pull-Down Kit (Thermo Scientific Pierce, Rockford, IL, USA) following the manufacturer’s instructions. The experiments were performed as described in detail previously [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…FMDV is the most economically important and highly contagious veterinary pathogen, affecting long-term livestock health and international trade ( Grubman and Baxt, 2004 ; Dong et al., 2021 ). Although the outbreaks of FMD have been effectively controlled by various prophylactic vaccines and animal culling ( Jamal and Belsham, 2013 ; Abdullah et al., 2020 ), the potential for future outbreaks warns us of the need for safe and effective therapeutics to prevent viral infections. Growing researches have demonstrated that many viruses can induce endoplasmic reticulum (ER) stress-mediated autophagy to regulate viral replication and pathogenesis ( Lv et al., 2015 ; Sharma et al., 2017 ; Lee et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%